2021
DOI: 10.3389/fonc.2021.803266
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia and Cancer, Friend or Foe? A Narrative Review

Abstract: Cancer remains the leading cause of death worldwide with close to 10 million deaths reported annually. Due to growth of the advanced age cohort in our population, it is predicted that the number of new cancer cases diagnosed between now until 2035 is to reach potentially 24 million individuals, a staggering increase in a relatively short time period. For many solid tumors, surgical resection along with chemotherapy is the best available approach to a potential cure which leads to almost 80% of cancer patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Given that the majority of patients with GC will experience at least one anesthesia, the effects of different anesthetic approaches and drugs on the cancer outcomes of GC patients have been increasingly regarded as a research priority. The choices of anesthetic approach (general vs. neuraxial anesthesia), anesthetic agent (inhalational vs. intravenous), and accompanying prescribed analgesic drugs have long been assumed to influence the risk of cancer recurrence [ 24 ]. However, the available limited evidence regarding the effects of these techniques and drugs on cancer recurrence in GC has been inconclusive ( Supplementary Table S2 ).…”
Section: Perioperative Events and Prognosis Of Gc Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the majority of patients with GC will experience at least one anesthesia, the effects of different anesthetic approaches and drugs on the cancer outcomes of GC patients have been increasingly regarded as a research priority. The choices of anesthetic approach (general vs. neuraxial anesthesia), anesthetic agent (inhalational vs. intravenous), and accompanying prescribed analgesic drugs have long been assumed to influence the risk of cancer recurrence [ 24 ]. However, the available limited evidence regarding the effects of these techniques and drugs on cancer recurrence in GC has been inconclusive ( Supplementary Table S2 ).…”
Section: Perioperative Events and Prognosis Of Gc Patientsmentioning
confidence: 99%
“…However, the available limited evidence regarding the effects of these techniques and drugs on cancer recurrence in GC has been inconclusive ( Supplementary Table S2 ). Regarding anesthetic techniques, epidural anesthesia has populated in recent years in oncological surgery [ 24 ]. A small number of retrospective studies have reported the relationships between epidural anesthesia and GC patient outcomes with conflicting results.…”
Section: Perioperative Events and Prognosis Of Gc Patientsmentioning
confidence: 99%
“…DEX is a highly selective α2 adrenoreceptor agonist and has multiple pharmacologic effects, including hypnosis, analgesia, sedation, and anxiolysis. α2 adrenergic receptors are expressed on both immune cells and tumors, which indicates that DEX may affect the balance of the immune system and tumorigenesis [ 176 , 177 ]. According to a meta-analysis of patient studies by Wang et al, the intraoperative use of DEX infusion increases the numbers of NK cells, B cells, and CD4 + T cells and the ratios of CD4 + /CD8 + and Th1/Th2 cells, while the number of CD8 + T cells is significantly decreased [ 178 ].…”
Section: The Perioperative Effects Of Anesthetics On Cancer Recurrencementioning
confidence: 99%
“…Firstly, local anesthetic was involved in mediating tumor growth and metastasis via influencing the biological behavior of tumor cells. Local anesthetics inhibit cell proliferation by inhibiting catecholamines release [ 10 , 11 ]. RA also reduces the excitability of cancer cells by blocking voltage-gated sodium channels, thereby reducing the metastatic potential [ 12 ].…”
Section: Introductionmentioning
confidence: 99%